Digital audio's final frontier. - Putzeys, B. (IEEE spectrum)
Digital technology continues its march from media like CDs and DVDs toward your audio speakers. Today, amplifiers based on digital principles are already having a profound effect on equipment efficiency and size. They are also beginning to set the standard for sound quality. What distinguishes Class D amplifiers from all others is that their power transistors are always operated either fully on or fully off. This is the only and complete definition of Class D. In their most obvious form, these systems will be able to accept a stream of bits from a CD or MP3 player and convert it into an analog signal that can drive a set of speakers.